A preliminary histological study, in an experimental murine model, of gastritis induction, compared to the protective effect of a biological preparation - Sergiu Orășan - Alic; Diana Brezovan; Eugenia Dumitrescu; Florin Muselin; Mihai Folescu; Daiana Ionela Cocos; Alexandru O. Doma; Romeo T. Cristina (Medicamentul Veterinar, 2023)
Peptic ulcer disease is a chronic condition that affects a significant number of people worldwide, estimated at approximately 10% of the global population. This is the result of an imbalance between aggressive factors, such as gastric juice and its increased acidity, and the defense mechanisms of the lining of the stomach and small intestine. Aspects such as exposure to certain substances or infection with bacteria such as Helicobacter pylori (H. pylori) are considered triggers in the development of peptic ulcers. Risk factors include frequent use of non-steroidal anti-inflammatory drugs (NSAIDs) and high levels of stress. Conventional treatments for peptic ulcers include proton pump inhibitors (PPIs) and histamine-2 (H2) receptor antagonists, which are effective in decreasing gastric acid secretion. However, these treatments may be associated with side effects and may lead to recurrences or unwanted interactions with other medications. In contrast, natural approaches and complementary therapies have gained popularity in the management and treatment of peptic ulcers. Medicinal plants and their active compounds have been recognized for their anti-inflammatory and protective properties of the stomach lining. Some plants such as Curcuma longa or Angelica keiskei have been studied for their potential to reduce inflammation and promote ulcer healing, as well as other natural preparations such as royal jelly or propolis, derived from beekeeping. For example, royal Jelly is known for its anti-inflammatory and antimicrobial properties, which can help reduce irritation of the gastric mucosa and heal ulcers. Angelica keiskei, with its active compounds, has demonstrated the ability to protect the mucosa and reduce the excessive production of gastric acid. Turmeric, rich in curcumin, is another ingredient studied for its anti-inflammatory and antioxidant effects, which may support healing and reduce peptic ulcer symptoms.